Anti-clericalism in pre-independence Greece c 1750–1821 - Clogg, Richard (Studies in church history, 1976)
Writing in the 1820s, during the Greek war of independence, of his tour of the Peloponnese Sir William Gell noted that there was ‘a saying common among the Greeks, that the country labours under three curses, the priests, the cogia bashis, and the Turks; always placing the plagues in this order’. This kind of sentiment is a commonplace of the sources, both Greek and non-Greek, relating to pre-independence Greece and it is clear that anti-clericalism was deeply rooted, and not only among the intelligentsia, but among virtually all classes of Greek society. The prevalence, and indeed, the virulence of anti-clerical attitudes in Greece during the pre-independence period must call into question the view still advanced by authorities on this period that the church played a central role in the forging of the Greek national movement. Sir Steven Runciman, for instance, has written that ‘Hellenism survived, nurtured by the Church, because the Greeks unceasingly hoped and planned for the day when they would recover their freedom’, while Douglas Dakin has written that ‘so closely knit was the national existence of the Greeks with their Church that in their liberation movement there was no hostility to the Greek patriarchate comparable to that which the Italians displayed towards the Papacy’.2 Views of this kind also constitute the common currency of Greek historiography. D. A. Zakythinos, for instance, has written that ‘it is universally admitted that die Church saved the Greek Nation during the dark years of slavery’. But he goes on to say that earlier and more recent historians, the ‘healthy minded’ among them, as well as those having ‘certain special political tendencies’, do not subscribe to such a view in toto. He quotes the founding father of modern Greek historiography, Konstantinos Paparrigopoulos, to the effect that ‘the ancestral religion did not cease to constitute one of the principal moral mainsprings of Hellenism, but it did not itself alone constitute Hellenism’.